Association between Generalized Anxiety Disorder and Premenstrual Dysphoric Disorder in a Diagnostic Interviewing Study - Yen, Ju-Yu (Int J Environ Res Public Health, 2020)
Background: Premenstrual dysphoric disorder (PMDD) demonstrates predictable, cyclic, affective and somatic symptoms that are aggravated in the late luteal phase and are resolved by menstruation. Generalized anxiety disorder (GAD) is characterized by excessive and persistant worry. The present study aims to evaluate the association between PMDD and GAD. The fluctuations of behavior inhibition, anxiety, depression, and irritability were also evaluated during the menstrual cycle among women with PMDD and healthy women. Methods: There were 100 women diagnosed with PMDD based on a psychiatric interview and on a prospective evaluation in three menstrual cycles. A total of 96 healthy women were recruited as controls. Each individual’s GAD diagnosis, behavior inhibition, behavior activation, depression, anxiety, and irritability were assessed in both luteal and follicular phases. Results: The odds ratio of women with GAD having PMDD was 7.65 (95% CI: 1.69–34.63) in relation to those without it. This association was partially mediated by behavior inhibition and irritability and was completely mediated by depression. Women with PMDD and GAD had higher anxiety during the luteal phase and higher PMDD severity, depression, and irritability than those without GAD in the follicular phase. There is no difference in anxiety, depression, or irritability between the luteal and follicular phases among women with PMDD and GAD. Conclusions: Women with GAD were more likely to have PMDD. Anxiety, depression, and irritability symptoms in women with PMDD and GAD were not relieved in the follicular phase. Thus, GAD should be assessed for women with PMDD. Their anxiety, depression, and irritability should be intervened not only in the luteal phase, but also in the follicular phase. Depression, irritability and behavior inhibition mediated the association between PMDD and GAD. Intervening with these mediators to attenuate GAD and PMDD comorbidity should be researched in the future.